Orexin Receptor Type-1 Couples Exclusively to Pertussis Toxin-Insensitive G-Proteins, While Orexin Receptor Type-2 Couples to Both Pertussis Toxin-Sensitive and -Insensitive G-Proteins - Yun Zhu; Yoshihiro Miwa; Akihiro Yamanaka; Toshihiko Yada; Megumi Shibahara; Yoichiro Abe; Takeshi Sakurai; Katsutoshi Goto (Elsevier, 2003)
Signal transduction pathways of orexin receptors were examined using a nerve-like cell line transfected with orexin receptor type-1 (OX1R) and orexin receptor type-2 (OX2R). Forskolin-stimulated cyclic adenosine 3,5-monophosphate (cAMP) accumulation in OX2R-expressing cells was inhibited by orexin in a dose-dependent manner, and the effect was abolished by pretreatment with pertussis toxin (PTX). The inhibitory effect of orexin on forskolin-stimulated cAMP accumulation was not observed in OX1R-expressing cells. Administration of orexin to these cells resulted in a transient increase of intracellular calcium concentration ([Ca2+]i). Orexin-stimulated increases in [Ca2+]i in OX1R- or OX2R-expressing cells were not affected by the PTX pretreatment. These observations suggest that OX1R couples exclusively to PTX-insensitive G-proteins, while OX2R couples to both PTX-sensitive and -insensitive G-proteins. To examine the relative contributions of these G-proteins in OX2R-mediated activation of neurons, we used histaminergic tuberomammillary nucleus neurons, in which OX2R is abundantly expressed. We found that a phospholipase C (PLC)-inhibitor, U73122, inhibits orexin-mediated neuronal activation, but PTX showed no effect on it. This suggests that although OX2R couples to multiple G-proteins, activation of neurons by orexins through OX2R is mediated via a PTX-insensitive, PLC dependent pathway.